2022
DOI: 10.3390/antibiotics11040531
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Danofloxacin Treatment on the Development of Fluoroquinolone Resistance in Campylobacter jejuni in Calves

Abstract: Campylobacter is a leading cause of foodborne gastroenteritis. Recent studies have indicated a rise in fluoroquinolone-resistant (FQ-R) Campylobacter in cattle, where FQ is used to control bovine respiratory disease (BRD). To assess the effect of danofloxacin treatment on the development of FQ-resistance in C. jejuni, 30 commercial calves were divided into Group 1, Group 2, and Group 3 (n = 10), and were all inoculated orally with FQ-susceptible (FQ-S) C. jejuni; seven days later, Group 3 was challenged with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(39 citation statements)
references
References 73 publications
4
35
0
Order By: Relevance
“…This finding indicated that a single dose subcutaneous enrofloxacin treatment, as employed in the current study, did not result in any detectable level of FQ-resistance development from FQ-susceptible C. jejuni inhabiting the intestine of calves. As mentioned above, highly similar results were obtained with another FQ-antibiotic (danofloxacin) treatment of calves in a recent experimental study conducted by our research group [ 38 ], as well as in a field study in which feedlot cattle were treated with a single subcutaneous dose (7.5 mg/kg) of enrofloxacin for metaphylactic purposes [ 44 ].…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…This finding indicated that a single dose subcutaneous enrofloxacin treatment, as employed in the current study, did not result in any detectable level of FQ-resistance development from FQ-susceptible C. jejuni inhabiting the intestine of calves. As mentioned above, highly similar results were obtained with another FQ-antibiotic (danofloxacin) treatment of calves in a recent experimental study conducted by our research group [ 38 ], as well as in a field study in which feedlot cattle were treated with a single subcutaneous dose (7.5 mg/kg) of enrofloxacin for metaphylactic purposes [ 44 ].…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, it is crucial to assess if the FQ treatment regimen can be optimized to minimize the selection pressure on Campylobacter and the magnitude of FQ-resistance in cattle. As shown in our recent study [ 38 ], single dose subcutaneous danofloxacin (an FQ antibiotic) treatment did not cause any quantifiable level of de novo resistance in FQ-susceptible C. jejuni strains in the intestine of either healthy or BRD-induced calves. In that study, the vast majority of calves were naturally colonized (an un-ideal situation for experimental purposes) by FQ-resistant C. jejuni prior to the experimental inoculation, which experienced a sharp but brief spike after the FQ injection.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations